THE EFFECT OF USING COMPOSITE PICTURES ON READING COMPREHENSION ACHIEVEMENT - Fatma Dewani Harahap (JURNAL EDUSCIENCE (JES), 2021)
Reading Comprehension is the ability to read text, process it and understand the meaning. It relies on two, interconnected abilities: Word reading be able to decode the symbols on the page and language comprehension being able to understand the meaning of words and sentences . In fact, students generally feel bored and unmotivated in learning English especially in reading skill because English is different from Indonesian so that the students have difficulty in understanding reading English text. They do not know the meaning of some words in the text. Therefore, the teacher’s role becomes important in the teaching and learning process especially in teaching reading. Therefore, appropriate media should be chosen to motivate their students not only to read the text but also comprehend what they read. One of the media that can be used and applied by the teacher is Composite Pictures. A Composite Picture is a large single picture which shows a scene in which a number of people can be seen doing several things. Thus, to know whether or not there was a significant effect of using Composite Pictures on reading comprehension achievement; Composite Pictures was used as media in teaching reading in this research.